Synonymizations and typifications in Stomatanthes (Asteraceae: Eupatorieae, Eupatoriinae) from South America - Rebouças, Natanael Costa; Amorim, Vivian Oliveira; Grossi, Mariana Andrea; Roque, Nádia; Bünger, Mariana De Oliveira (Phytotaxa, 2025)
During a taxonomic review of Stomatanthes (Asteraceae, Eupatorieae) in South America, we identified that it was necessary to carry out several nomenclatural acts according to the International Code of Botanical Nomenclature. After analyzing protologues, type materials and examining about 400 specimens, deposited in 45 herbaria, Seven lectotypes were indicated and six new synonyms were proposed.